Освітня міграція. Економічні та соціальні аспекти - Пантелєєв, Михайло Сергійович; Побережна, Наталія Миколаївна (Херсонський державний університет, 2014)
У статті проведено аналіз кількісних та структурних змін у чисельності студентів денної та заочної форм навчання у ВНЗ України з країн Азійського регіону. Розраховано економічний ефект від навчання іноземних студентів з країн Азійського регіону за 2012/13 та 2013/14 навчальні роки. Визначено структуру сумарного ефекту від експорту освітніх послуг.

The dynamics of quantitative and structural changes in the number of full-time students and distance learning students from CIS countries of Asia region in universities Ukraine was analyzed. The economic effect from foreign students’ education from the CIS countries of the Asian region in the 2012/13 academic year in the 2013/14 academic year was calculated. The structure of the cumulative effect of the export of educational services was determined.
Education migration. Economic and social aspects
Keywords: освітня міграція; експорт освітніх послуг; динаміка змін; контингент іноземних студентів; економічний ефект; educational migration; export of educational services; dynamics of changes; foreign students; economic effect